Higher long-term mortality in patients with concomitant acute coronary syndrome and aortic stenosis. (3rd October 2022) - Chew, N W S; Zhang, A; Koh, S; Ong, J L; Kong, G; Lim, O; Kuntjoro, I; Kong, W; Low, A; Lee, C H; Chan, M Y; Yeo, T C; et al.
Abstract: Background: Aortic stenosis (AS) and acute coronary syndrome (ACS) share similar cardiovascular risk factors, and their concomitant presentation is increasing in incidence with the aging population. Yet literature regarding the prognosis of patients with concomitant ACS and AS remains scarce. Methods: This retrospective cohort study examined consecutive patients presenting with ACS (ST-segment elevation myocardial infarction [STEMI] and non-STEMI [NSTEMI]) and concomitant AS between 1 January 2011 and 31 March 2021 in a tertiary hospital. The cohort was divided into mild, moderate and severe AS based on index echocardiogram. The primary outcome was all-cause mortality. Kaplan-Meier curves were constructed to compare all-cause mortality among the three groups of patients, based on ACS type and left ventricular ejection fraction (LVEF). Multivariable Cox regression was performed to identify independent predictors of all-cause mortality. Results: Of a total of 563 patients, 264 had mild (46.9%), 193 moderate (34.3%) and 106 severe AS (18.8%). The mean follow-up duration was 2.5 (± 2.4) years. Majority of patients (72.5%) presented with NSTEMI. Patients with moderate and severe AS had higher rates of all-cause mortality compared to those with mild AS (49.7% vs. 51.4% vs. 35.6% respectively, p=0.002). Concomitant moderate (HR 1.439, 95% CI 1.012–2.048, p=0.043) and severe AS (HR 1.844, 95% CI 1.159–2.933, p=0.010) were independent predictors of all-cause mortality after adjusting for age, gender, LVEF, ACS type, chronic kidney disease, diabetes, hypertension, coronary artery bypass grafting and aortic valve replacement as a time-dependent variable. The Kaplan-Meier curves demonstrated excess mortality in moderate and severe AS, compared to the mild AS group (p<0.001), with similar survival trends observed in the STEMI and the NSTEMI groups, as well as those with preserved LVEF. Conclusion: Regardless of the ACS presentation type, long-term excess mortality in those with concomitant moderate or severe AS was observed. The adverse prognosis typically observed in patients with concomitant severe AS, in the setting of ACS, extends to patients with moderate AS. Funding Acknowledgement: Type of funding sources: None.